The SILL revisited in light of the S2R model of language learning. Issue 5 (20th October 2018) - Papadopoulou, Iris; Kantaridou, Zoe; Platsidou, Maria; Gavriilidou, Zoe
ABSTRACT: The Strategy Inventory for Language Learning (SILL) [Oxford, R.L. 1990. Language Learning Strategies: What Every Teacher Should Know. Boston: Heinle and Heinle] has been a widely used instrument for self-assessing the frequency of language learning strategy use across cultures and levels of education for some 30 years. Despite the fact that its six-factor solution has not been confirmed, it has displayed acceptable reliability across cultures and translations. In the present study, we attempt to demonstrate a new factor solution for the Greek version of the SILL which is in line with the S 2 R model of language learning. Our sample consisted of 1308 primary and secondary school students from public schools in the regions of Northern Greece. The SILL v7.0 was used with four additional items selected and adapted from SILL v5.0. Exploratory and confirmatory factor analyses revealed six factors which explained 42.48% of the total variance and demonstrated good or adequate reliability. The first two factors indicate the metastrategies of 'monitoring cognition for progress' and 'obtaining resources'. The other four factors indicated strategies of 'deep cognitive processing', 'using resources', 'surface cognitive processing' and 'overcoming gaps of knowledge'. We compare our results with factor solutions of the SILL obtained in earlier studies and we discuss implications for the development of new instruments to better accommodate the S 2 R model of language learning.